Effect of Trehalose and Sucrose in Post-thaw Quality of Crassostrea angulata Sperm - Anjos, Catarina; Santos, Ana Luísa; Duarte, Daniel; Matias, Domitília; Cabrita, Elsa (Frontiers in Physiology, 2021)
Sperm cryopreservation can be a helpful tool in reproductive management and preservation of biodiversity. However, the freezing methodologies lead to some damage in cells structure and function, that may compromise post-thaw sperm activity. Cryoprotectant supplementation with sugars proved to be a successful strategy to reduce cryodamage in sperm of several species, once allowing to stabilize the plasma membrane constituents. Therefore, this work intends to understand the effects of sugars in the plasma membrane, DNA integrity, and oxidative response during Portuguese oyster sperm cryopreservation. Three cryoprotectants solutions with an initial concentration of 20% DMSO and 20% DMSO complemented with 0.9 M trehalose or sucrose, in artificial seawater were employed. Sperm samples of mature males were individually collected and diluted 1:10 (v/v) in artificial seawater, followed by cryoprotectants addition (1:1 (v/v)). Thereafter, sperm was loaded into 0.5 mL straws, maintained at 4ºC for 10 min, frozen in a programmable biofreezer at -6ºC/min from 0 to -70°C and stored in liquid nitrogen. Samples were thawed in a 37°C bath for 10s. Several techniques were performed to evaluate post-thaw quality. Sperm motility and DNA integrity were analyzed using CASA (computer assisted sperm analysis) software and comet assay. Flow cytometry was employed to determine membrane and acrosome integrity and to detect intracellular reactive oxygen species (ROS) and apoptosis activity. Lipid peroxidation was determined by MDA (malondialdehyde) detection using spectrophotometry. Sperm antioxidant capacity was evaluated through glutathione peroxidase, glutathione reductase and superoxide dismutase. Motility was not affected by the extenders containing sugars; these compounds did not reduce the DNA damage. However, both trehalose and sucrose protected cells plasma membrane by increasing cell viability and significantly reducing MDA content. The same finding was observed for the reactive oxygen species, where live cells registered significantly lower levels of ROS in samples cryopreserved with sugars. The activity of antioxidant enzymes was higher in treatments supplement with sugars, although not significant. In conclusion, the addition of sugars, seems to play an important role, in protecting the Crassostrea angulata sperm membrane during cryopreservation, showing potential to improve the post-thaw sperm quality and protect the cells from cryoinjuries.